Synthesis of Benzylpenicillin esters and evaluate the change in the anti-bacterial effects by Docking and bacteriological study - Abdulrahman alsheikhly, Omar; R. Ganjo, Aryan; Sardar Abdulrahman, Hayman; Y. Issa , Sanaa (Diyala Journal of Medicine, 2024)
Background: Benzylpenicillin is an antibiotic that possesses effectiveness mainly against gram-positive and some gram-negative bacteria. The carboxylic acid of beta-lactam is essential for its antibacterial activity. However, many prodrugs have been produced through the esterification of this carboxylic acid group, like Pivampicillin. Objective: To evaluate the antibacterial effects of Benzylpenicillin when the free carboxylic acid mask with different chemical groups of different polarity. Patients and Methods: Four Benzylpenicillin derivatives (compounds p1-p4) were chemically synthesized through the esterification of the carboxylic acid group with different groups of different polarity, and the antibacterial activities were examined by docking and bacteriological studies. Results: All the compounds showed different antibacterial results. The docking results showed that; the compound of the highest polarity (compound p1) has the best Binding energy. Also; The results of in vitro antibacterial activity showed that; compound p1 had the largest zones of inhibition and the highest antibacterial activity among all the other compounds. Conclusion: Masking the free carboxylic acid of benzylpenicillin with polar group will enhance the antibacterial activity.